Waqf fundraising management: a conceptual comparison between traditional and modern methods in the waqf institutions - Muhammad Shulthoni; Norma Md Saad (Indonesian Journal of Islam and Muslim Societies, 2018)
This paper focuses on the theoretical structure of funding for Islamic philanthropy, especially waqf. Waqaf is projected to play further significant role to tackle present social problems, where financial sustainability has become one of the foremost challenges faced by awqaf institutions. There is a need to study various models of fundraising that could be applied to reform awqaf institutions. Employing content analysis approach, this paper analyses traditional and modern structures of fundraising that are applicable for development and management of waqaf fundraising: istibdal, h}ukr, ijaratayn, venture philanthropy of waqf model (VPWM), value-based capital model of waqf (VBCMW), and social enterprise waqf fund model (SEWF).The discussions are expected to be able to contribute towards boosting a better fundraising management of awqaf institutions in Muslim communities as well as countries.Makalah ini fokus pada struktur teoritis pendanaan untuk filantropi Islam, terutama wakaf. Wakaf diproyeksikan untuk memainkan peran penting lebih lanjut untuk mengatasi masalah sosial saat ini, di mana keberlanjutan keuangantelah menjadi salah satu tantangan utama yang dihadapi oleh lembaga-lembagaawqaf. Ada kebutuhan untuk mempelajari berbagai model penggalangan danayang dapat diterapkan untuk mereformasi institusi awqaf. Dengan menggunakanpendekatan analisis isi, makalah ini menganalisis struktur penggalangan danatradisional dan modern yang berlaku untuk pengembangan dan pengelolaanpenggalangan dana wakaf: istibdal, h}ukr, ijaratayn, venture philanthropy ofwaqf model (VPWM), value-based capital model of waqf (VBCMW), dan socialenterprise waqf fund model (SEWF). Diskusi diharapkan dapat berkontribusiuntuk meningkatkan manajemen penggalangan dana yang lebih baik darilembaga awqaf di komunitas Muslim serta negara.